Antibiogram Pattern of Bacterial Isolates from Bovine and Bubaline Semen in Karnataka - V C, Nithyananda; Murag, Shivaraj; K M, Chandrashekar; B P, Shivashankar; S, Isloor; D, Rathnamma (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
To avert bacterial contamination in semen, antibiotics are added. Inspite of addition of conventional antibiotics, extended and frozen semen samples from bulls have been reported to contain a number of bacterial contaminants which may be due to the antimicrobial resistance because of indiscriminate usage of antibiotics. The present study was conducted to know the antibiotic susceptibility pattern of the bacterial isolates from neat semen and frozen semen straws of cattle and buffalo bulls, collected from three semen stations (Farm A, B & C) of Karnataka. A total of twenty eight Holstein Friesian (HF) bulls, fourteen Murrah and two Surti buffalo bulls were selected for the study. Three time sample collections from each farm at a gap of 15 days were carried out. A total of 205 bacterial isolates were obtained from 264 samples of neat and frozen semen from three different farms (Farm A 49, Farm B 63 and Farm C 93). All isolates were, highly sensitive to newer generation antibiotics Piperacillin-Tazobactam, Imipenem and completely resistant to routinely used antibiotics Penicillin G, and Streptomycin.